2018
DOI: 10.3892/mmr.2018.9412
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of lncRNAs GM5524 and GM15645 involved in high‑glucose‑induced podocyte apoptosis and autophagy in diabetic nephropathy

Abstract: Diabetic nephropathy (DN) is an important microvascular complication of diabetes, and one of the leading causes of end-stage kidney disease. However, the mechanism of the DN pathogenic process remains unclear. Recently, long non-coding (lnc)RNA dysregulation has been regarded to cause the occurrence and development of various human diseases, although the functions of lncRNAs in human DN are poorly understood. The authors' previous study using microarray analysis identified hundreds of dysregulated lncRNAs in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Apoptosis was a process whereby cells died in a controlled manner, which was involved in the development of DN. 39,40 Podocyte apoptosis is an important pathogenic alteration that leads to podocyte loss in DN. Previous studies have shown that the interaction between apoptosis and DN included complex pathways and molecular and confirmed the important role of apoptosis pathways in DN.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis was a process whereby cells died in a controlled manner, which was involved in the development of DN. 39,40 Podocyte apoptosis is an important pathogenic alteration that leads to podocyte loss in DN. Previous studies have shown that the interaction between apoptosis and DN included complex pathways and molecular and confirmed the important role of apoptosis pathways in DN.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of autophagy suppression in diabetic kidneys remain a matter of debate. Hyperglycemia was considered an autophagy suppressor in the studies with cultured podocytes [24,35], glomerular endothelial cells [36] and mesangial cells [37]. Kidney macroautophagy is regulated by mammalian target of rapamycin (mTOR) [8,38,39], AMP-activated protein kinase (AMPK) [8], SIRT1 [8], Wnt/β-catenin [40], and TGF-β [41] signaling pathways.…”
Section: Suppression Of Renal Autophagy In Diabetes: Markers and Mechmentioning
confidence: 99%
“…In terms of renal autophagy and apoptosis, lncRNA GM5524 expression was increased in DN mice and regulated these processes, upon stimulation with high glucose (Feng et al, 2018). GM5524 inhibits anti-apoptotic BCL2 expression and activates the LC3/ATG signaling pathway to promote autophagy (Feng et al, 2018).…”
Section: Lncrnas In Autophagy and Apoptosismentioning
confidence: 99%
“…In terms of renal autophagy and apoptosis, lncRNA GM5524 expression was increased in DN mice and regulated these processes, upon stimulation with high glucose (Feng et al, 2018). GM5524 inhibits anti-apoptotic BCL2 expression and activates the LC3/ATG signaling pathway to promote autophagy (Feng et al, 2018). LncRNA GAS5 is also a proapoptotic lncRNA, in which GAS5 promoted the human renal tubular epithelial cells apoptosis under high glucose environment (Lv et al, 2019) In contrast to that, lncRNA GM15645 expression was low in DN mice and podocyte cells upon stimulation of high glucose, and this lncRNA acts opposite to lncRNA GM5524 in the regulation of podocyte cells apoptosis and autophagy (Feng et al, 2018).…”
Section: Lncrnas In Autophagy and Apoptosismentioning
confidence: 99%